2023
DOI: 10.1002/ldr.4858
|View full text |Cite
|
Sign up to set email alerts
|

Mapping soil organic matter and identifying potential controls in the farmland of Southern China: Integration of multi‐source data, machine learning and geostatistics

Bifeng Hu,
Hanjie Ni,
Modian Xie
et al.

Abstract: Soil organic matter (SOM) plays a critical role in terrestrial ecosystem functioning and is closely related to many global issues like soil fertility, soil health and climate regulation. Therefore, obtaining accurate information on the spatial distribution of SOM and its potential controlling factors is of global interest. However, this remains a great challenge since SOM is affected by numerous natural and anthropogenic factors and usually showed strong heterogeneity. In this study, we collected a total of 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 112 publications
0
1
0
Order By: Relevance
“…In this study, K-nearest neighbor analysis is used to determine the expansion constants from different centers, which overcomes the shortage of the same weight of environmental variables in different spatial directions in the traditional model, which describes the local information in detail and effectively improves the prediction, accuracy, and generalization ability [25]. Our study demonstrated that the RF model achieved the highest prediction accuracy for mapping the SOM of farmland in Huang-Huai-Hai Plain, which is consistent with the farmland in southwest China [7], northeast and North Plain China [24], and Nepal [20]. This is owing to the RF having fewer constraints on sample collection and the ability to deal with robust outliers [12,48,64].…”
Section: Comparison Of Prediction Performance Of Different Modelsmentioning
confidence: 53%
See 2 more Smart Citations
“…In this study, K-nearest neighbor analysis is used to determine the expansion constants from different centers, which overcomes the shortage of the same weight of environmental variables in different spatial directions in the traditional model, which describes the local information in detail and effectively improves the prediction, accuracy, and generalization ability [25]. Our study demonstrated that the RF model achieved the highest prediction accuracy for mapping the SOM of farmland in Huang-Huai-Hai Plain, which is consistent with the farmland in southwest China [7], northeast and North Plain China [24], and Nepal [20]. This is owing to the RF having fewer constraints on sample collection and the ability to deal with robust outliers [12,48,64].…”
Section: Comparison Of Prediction Performance Of Different Modelsmentioning
confidence: 53%
“…Furthermore, SOM is tightly linked to human activities in dryland agroecosystems, and covariates characterizing human activities such as tillage systems and fertilization methods were not included in the model predictions due to limited data acquisition. The practice has proven that agricultural activities such as rotation, irrigation, and fertilization significantly impact SOM [3,7,65]. Therefore, finding more auxiliary variables with a strong correlation with the SOM and alternative factors that can represent human activities as model inputs will be among the important ways in which to improve the accuracy of SOM prediction.…”
Section: Comparison Of Prediction Performance Of Different Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PLS-SEM was used to explore composite factors affecting biomass variation and associative interactions and to understand regional biomass variation in driving factors using Smart PLS 4.0.9.4 [57]. Topographical sampling maps were generated using ArcGIS 10.7 (ESRI ® ArcMap™ 10.7) [58].…”
Section: Discussionmentioning
confidence: 99%